Characterization of Auditory Disability and Its Relation to the Resilience - GarcÃƒÂa, Bibian Bibeca Bumbila; CedeÃƒÂ±o, HernÃƒÂ¡n AndrÃƒÂ©s CedeÃƒÂ±o; Chica, Tatiana Katiuska Moreira; RÃƒÂos, Yaritza Rossana Parrales (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the work is to establish the characterization of the auditory disability and its relationship with resilience at the Technical University of ManabÃ. The article shows a conceptual analysis related to the inclusion and social integration of disabled students. Based on the fact that the person with disabilities grows and develops in the same way as that of people without disabilities and what usually happens is that disabled people are rejected and discriminated against based on a prefabricated and erroneous conceptualization of these people. The results associated with the application of the SV-RES test prepared by the researchers are shown (Saavedra & Villalta, 2008b). Characterization of the auditory deficit is made in the students, and the limitations that derive from it are pointed out. We analyze the particularities related to communication with students who have a hearing disability and resilience in this type of student, where some personal highlights that in this sense constitute an example of resilience. Finally, the results related to the study of the relationship between students hearing disability and the level of resilience dimensions are shown.